The impact of anal sphincter injury on perceived body image. (May 2017) - Iles, David; Khan, Rabia; Naidoo, Kristina; Kearney, Rohna; Myers, Jenny; Reid, Fiona
Abstract: Objective: Obstetric anal sphincter injury is common but the effect on body image is unreported. The aim of this study was to explore patient perceived changes in body image and other psychological aspects in women attending a perineal follow-up clinic. Study design: This retrospective study analysed women's responses to a self-reported questionnaire. Consecutive women with anal sphincter injury who attended a United Kingdom Maternity Hospital perineal follow-up clinic between January 1999 and January 2012 were identified and the records obtained and reviewed. Multivariate regression analyses were performed to examine variables influencing self-reported change in body image. Results: Questionnaires and operation notes were analysed from 422 women who attended at a median of four months after delivery. 222 (53%) reported a change in body image with 80 (19%) reporting lower self-esteem and 75 (18%) a change in their personality due to the change in body image. 248 (59%) perceived an anatomical change due to the delivery. Factors associated with increased likelihood of reporting a change in body image were reporting a perceived change in anatomy due to the delivery, adjusted OR 6.11 (3.56–10.49), anal incontinence, OR 1.97 (1.16–3.36), and delivery by forceps, OR 2.59 (1.23–5.43). Conclusions: This is the first study to quantify body image changes in women after anal sphincter injury sustained in childbirth. These were found to be very common, affecting up to 50% of women. The study has several limitations but it does highlight the significant psychosocial problems of negative self-esteem and personality changes associated with a perceived change in body image that has not previously been reported. It also outlines the further research questions that need to be addressed.